Evaluation of a concurrent‐operant demand assessment to determine task preference. (17th August 2020) - Lloveras, Lindsay A.; Call, Nathan A.; Bourret, Jason C.; Slocum, Sarah K.
Abstract: We conducted a concurrent‐operant demand assessment (CODA) to identify a hierarchy of preference for demands in 17 individuals who exhibited problem behavior. We presented demands in pairs, with selection between demands serving as the dependent variable. The reinforcing efficacy of escape from the most‐ and least‐selected demands from the CODA was evaluated for 7 participants using progressive‐ratio (PR) schedules. Outcomes from the PR analysis corresponded with the rank order of demands from the CODA. Four of these seven participants were subsequently exposed to a brief CODA with only two items, which consisted of successive presentations of the most‐ and least‐selected demands from the CODA. Outcomes of the brief CODA corresponded with the PR and CODA for 3 out of 4 participants. These results suggest that the CODA might be an effective technology to determine a hierarchy of preference for demands for assessment and treatment purposes.